Planning Support Systems' Application Bottlenecks - Georgia Pozoukidou (European Regional Science Association (ERSA), 2006)
Information technology, urban models and decision support tools have been and will continue to be an integral part of the decision making process in planning. Despite their unambiguous significance, they are underutilized in professional practice. Literature suggests that there is a continuous failure to use complex planning methods like urban models, land use models, and decision support tools in agencies. At the same time there is little or no research on the reasons why there is such an underutilization of these tools in planning practice. As part of a larger project, this paper presents the results of a study on the applicability and effectiveness of a complex land use modeling tool in planning practice and agencies' decision making processes. The study intended to capture users' perspective and record their experiences when using the modeling tool. The basic research assumption was that there are certain functional and structural factors that could operate as obstacles, or bottlenecks, and block or delay the implementation of such systems. A questionnaire identifying these factors was developed and distributed to the participants. Ten U.S. Metropolitan Planning Organizations participated as users (of the land use modeling system) and were asked to evaluate the tool in the context of their planning and decision making practices. The results showed that if we set aside the considerable user expertise that is required to utilize urban land use models and PSS in general, there are factors that could prohibit the applicability or reduce the usability of these tools in practice. The main factors reported as potential bottlenecks were extensive data requirements, lack of operational support from PSS's provider and limited understanding of PSS's usability in planning tasks. Based on the research results there are suggestions regarding the development, application and dissemination of PSS in planning practice and agencies. Perhaps more importantly, this paper provides the planning scientific community with a useful understanding of the context, challenges and design choices involved when developing PSS that are intended to fulfill their dual role, as tools for planning practitioners that lack modeling experience and as instruments to facilitate a more democratic planning process.
Keywords: 330